Intelligent CALL, Granular Systems and Learner Data: Short Papers From Eurocall 2022 2022
DOI: 10.14705/rpnet.2022.61.1465
|View full text |Cite
|
Sign up to set email alerts
|

Edutainment: assessing students’ perceptions of Kahoot! as a review tool in French L2 classes

Abstract: Gamification is a method used to engage and motivate students virtually during the coronavirus pandemic. This paper reports on the use of Kahoot! as a review tool in French as a foreign language (L2) classes at Northern Caribbean University (NCU), Jamaica, as a means of formative assessment. Using the exploratory approach, it seeks to highlight students’ perceptions of this platform to enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
0
0
Order By: Relevance
“…These findings are consistent with studies conducted by Madden (2022b), Sadeghi et al (2023), and Le and Prabjandee (2023), that foreign language instructors have found innovative ways to incorporate new forms of assessments in their classrooms, especially during the Covid-19 pandemic. Madden's study focused on the integration of Kahoot!…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings are consistent with studies conducted by Madden (2022b), Sadeghi et al (2023), and Le and Prabjandee (2023), that foreign language instructors have found innovative ways to incorporate new forms of assessments in their classrooms, especially during the Covid-19 pandemic. Madden's study focused on the integration of Kahoot!…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, researchers and instructors have incorporated new forms of assessments, such as quizzes via Google Forms and Kahoot! games and interactive worksheets (Le & Prabjandee, 2023;Madden, 2022b;Sadeghi et al, 2023), which could all fall under the broad concept of gamificationthe application of game-like features and operations to non-game contexts to boost learner engagement and participation while interfacing with teaching content for both reinforcement and application of new knowledge.…”
Section: Introductionmentioning
confidence: 99%